Bubble Identification in Tehran's Stock Exchange: Evidence Based on Time-Varying Present Value Model - Gholam Reza kordestani; Ali Ashtab (بررسی‌های حسابداری و حسابرسی, 2010)
The little historical information of initial public offerings (IPOs) encounter investors with high risk because such companies don't exchange before. Information asymmetry between managers and potential investors in such companies are high and their stock are priced based on managerial information. The practical experience shows that investors rely on information such as earning per share (EPS) forecast and use it in stock pricing. This forecasts stated management expectations from the future performance of the company. So, the accuracy of this forecasts that is based for decision making are very important and earning forecast error is the main factor in secondary market performance. In this study we examine the relationship of earnings forecast error and abnormal rate of return of IPOs at Tehran stock exchange (TSE) for 104 companies during 1999 to 2005. The objective of this selected period is developing of stock exchange and increasing listed companies at the same times. Our results with multivariable cross sectional regression analysis demonstrated that earnings forecast errors are positively related to abnormal rate of return.